Improving health quality: does community-based education on health affected health quality? - Ahdad, Munadirah M.; Agit, Alamsyah (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Health is fundamental in everyday life; individuals can perform their activities without problems with a healthy body and mind. However, standard health procedures and knowledge might not have been known publicly by everyone without exception. Therefore, in this condition, experts such as academia, nurses, doctors, specialists, and practitioners are essential to educate and introduce basic health knowledge to people, especially those who live in rural areas. The importance of education is unlimited not only in the field of health but also in various and numerous fields of study and sectors; this paper empirically analyzes the importance of community-based education on health quality. Do people with primary education and knowledge have the same health quality as those without? Methods: This paper is qualitative and uses case studies and a literature review. This paper obtains its data through numerous relevant empirical studies and empirical data.Results: This study indicates that most people, especially in rural areas, need more basic health knowledge, explaining why they often use unfiltered river water and eat without washing their hands. Due to the habits the body has repeatedly endured, their health quality doesn’t affect their performance.Conclusion: The analysis does explain that those with primary health knowledge tend to have more capabilities in avoiding disease or common sickness and staying healthy for extended periods compared to those who don’t have basic health knowledge.